A PROSPECTIVE STUDY COMPARING THE FUNCTIONAL OUTCOME OF BIPOLAR HEMIARTHROPLASTY (BHA) VERSUS TOTAL HIP REPLACEMENT (THR) IN ELDERLY PATIENTS WITH FRACTURE NECK OF THE FEMUR (Journal of Medical & Health Sciences Review, 2025)
Objective: To compare the Functional Outcome of Bipolar Hemiarthroplasty (BHA) Versus Total Hip Replacement (THR) in Elderly Patients with femoral neck Fractures.Study Design: Prospective studyPlace and Duration of Study: Department of Orthopedics, Combined Military Hospital, Rawalpindi from Sep 2023 to Sep 2024Methodology: Fifty patients with displaced femoral neck fractures were included in the study. The patients were randomly allocated to be treated with either bipolar hip arthroplasty (BHA) or total hip replacement (THR). Functional assessment was carried out using Harris Hip Score (HHS) at two weeks, three months, six months, nine months and one year postoperatively.Results: During follow-up the mean Harris Hip Scores in BHA group were 57, 61.3, 65.1, 68.8 and 72.2 and in THR group the mean HHS were 72.4, 76.6, 80.6, 83.9 and 87 at fourteen days, three months, six months, nine months and one year respectively. Patients undergoing THR had a higher HHS than patients undergoing BHA. Post op pain and range of motion (ROM) were significantly improved in patients undergoing THA as compared to patients with BHA.Conclusion: Patients undergoing THR had a higher Harris Hip Score (HHS) than patients undergoing BHA. Thus, THR is a better option as compared to BHA based on our short-term functional outcome assessment using HHS.